2012
DOI: 10.1088/0951-7715/25/6/1753
|View full text |Cite
|
Sign up to set email alerts
|

Slicing the Sierpiński gasket

Abstract: Abstract. We investigate the dimension of intersections of the Sierpiński gasket with lines. Our first main result describes a countable, dense set of angles that are exceptional for Marstrand's theorem. We then provide a multifractal analysis for the set of points in the projection for which the associated slice has a prescribed dimension.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…for all lines ℓ with irrational slope. The intersections of these carpets with lines of rational slope was investigated in several papers; see [3,4] and references there. In particular, in those two papers it is shown that for the gasket and many other carpets S, there are many lines with a given rational slope that intersect S in a set of dimension > dim H (S) − 1.…”
Section: Some Applicationsmentioning
confidence: 99%
“…for all lines ℓ with irrational slope. The intersections of these carpets with lines of rational slope was investigated in several papers; see [3,4] and references there. In particular, in those two papers it is shown that for the gasket and many other carpets S, there are many lines with a given rational slope that intersect S in a set of dimension > dim H (S) − 1.…”
Section: Some Applicationsmentioning
confidence: 99%
“…Proof. The part (1) is clear, we only need to prove (2). By definition, π t µ is a measure supported on some slice of K with the form K ∩ ℓ β −t ,z for some z ∈ K. It is clear that, for all n ≥ 1 and each element A of A t n , the support of π t µ intersects the boundary of A in at most two points.…”
Section: 1mentioning
confidence: 99%
“…For A p , B q as in Conjecture 1.1, the set A p × B q is such an example, for which it is clear that certain lines parallel to the axes are exceptional for the slice result, and Conjecture 1.1 predicts that these lines are the only exceptions.There is a rich literature about generic slices of various fractal sets, see e.g. [2,7,8,20,26,28,29,37]. However, very little is known about specific slices, and there were few partial results concerning Conjecture 1.1 before the present paper.…”
mentioning
confidence: 95%
“…In general, the relation between the Hausdorff dimensions of a self-affine set E ⊂ R n and of its intersection with a hyperplane S has been studied by many authors (Bárány, Ferguson and Simon [1], Manning and Simon [10], for example). In a recent study by Kempton [9], it is proved that if E is a self-similar set with dim H E = s such that the similarities do not include rotations and that the orthogonal projection of the s-dimensional Hausdorff measure on E to a line θ is absolutely continuous with a bounded density, then H s−1 (E ∩ S) > 0 and hence, dim H (E ∩ S) ≥ s − 1 holds for almost all S perpendicular to θ.…”
Section: Definitionmentioning
confidence: 99%
“…Images of the mappings ϕ I,1 × ϕ J,1 (left) and ϕ I,1 × ϕ J,−1 (right). where |I| denotes the length b − a of the interval I = [a, b].…”
mentioning
confidence: 99%